2016
DOI: 10.1002/14651858.cd002249.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Clomiphene and other antioestrogens for ovulation induction in polycystic ovarian syndrome

Abstract: Analysis 2.1. Comparison 2 Antioestrogen versus antioestrogen, Outcome 1 Live birth rate (per woman

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 74 publications
3
56
0
Order By: Relevance
“…On the other hand, Misso et al 7 found comparable ovulation rates between CC and letrozole (RR, 0.94; 95% CI, 0.82-1.07; I 2 = 0%) while the pregnancy rate was higher in the letrozole group, albeit there was no evidence of significant difference (RR, 1.53; 95% CI, 0.91-2.58; I 2 = 50%). Brown et al 6 found no evidence of a difference between CC and tamoxifen in ovulation and pregnancy rates while finding higher rates of both when adding dexamethasone to CC compared with CC alone, and these results are also in agreement with our study results. In women with unexplained subfertility undergoing intrauterine insemination, a recent meta-analysis reported no difference in EMT between CC and letrozole (WMD, −0.84; 95% CI, −1.97 to 0.28) 68 .…”
Section: Comparison With Previous Reviewssupporting
confidence: 93%
“…On the other hand, Misso et al 7 found comparable ovulation rates between CC and letrozole (RR, 0.94; 95% CI, 0.82-1.07; I 2 = 0%) while the pregnancy rate was higher in the letrozole group, albeit there was no evidence of significant difference (RR, 1.53; 95% CI, 0.91-2.58; I 2 = 50%). Brown et al 6 found no evidence of a difference between CC and tamoxifen in ovulation and pregnancy rates while finding higher rates of both when adding dexamethasone to CC compared with CC alone, and these results are also in agreement with our study results. In women with unexplained subfertility undergoing intrauterine insemination, a recent meta-analysis reported no difference in EMT between CC and letrozole (WMD, −0.84; 95% CI, −1.97 to 0.28) 68 .…”
Section: Comparison With Previous Reviewssupporting
confidence: 93%
“…The antiestrogenic effect of CC may adversely affect the development of the endometrium, but the importance of this relative to implantation is uncertain . In a recent meta‐analysis, CC increased the odds of achieving clinical pregnancy compared with placebo, but the included studies were considered to be of low quality . Transient side effects like hot flushes and blurred vision are common.…”
Section: Resultsmentioning
confidence: 99%
“…However, the higher rate of miscarriage was not maintained for post ART pregnancies. Given that there were no post ART pregnancies among BMI‐matched studies, the higher rate of hormonal medications in PCOS may have masked the impact of obesity on miscarriage. We also note that the higher prevalence of miscarriage in PCOS was maintained in hyperandrogenic phenotypes and for women from Australia and New Zealand and Africa.…”
Section: Discussionmentioning
confidence: 99%